Sale Force Automation System / Chiang Ming Chin - Chiang, Ming Chin (2002)
This study of project is the fulfillment for WXET 3181 and WXET 3182. The entire project, named Sales Force Automation System (SFA System), involves developing a web based interaction system for the use of the sales representatives and administrator of a company. This system will be built in a simple, high quality and fast way by using certain tools. The objective for developing this SF A System is to keep track of the information about the customer, sale persons, sample movement, company and product. There will be a database which all data will be kept in the database and can be retrieved easily. The system also will include user friendly feature. In consideration of providing these advance features, Active Server Pages 3.0 has been chosen as the developing language, with the database support by Microsoft Access 2000, in the platform of Windows 2000, running with server IIS 5.0. Besides, to guarantee the feasibility and accuracy of the final production, the Waterfall with prototyping methodology ha been utilized throughout the stages of the entire development progress. With the distinct division of two modules, which is the administration and the sales representatives Area Planning module , the entire operation of SFA system is manageable and systematic, with each performing it respective roles. With reference and review from the other systems, the additive enhancement of feature and cautious consideration of the existing constraint in real working environment, is expectedly leading this project to the future implementation in the faculty, with minimum limitations.